Pre-treatment of Lignocellulose Wates to Improve Ethanol Production from Different Kinds of Agro Residue: A Review - Singh, Devendra Pratap; Trivedi, Rakesh K. (National Geographical Journal of India, 2022)
Lignocelluloses are often a major or sometimes the sole components of different waste streams from various industries, forestry, agriculture and municipalities. Hydrolysis of these materials is the first step for either digestion to biogas (methane) or fermentation to ethanol. However, enzymatic hydrolysis of lignocelluloses with no pretreatment is usually not so effective because of high stability of the materials to enzymatic or bacterial attacks. Effective parameters in pretreatment of lignocelluloses, such as crystallinity, accessible surface area, and protection by lignin and hemicellulose are described first. Then, several pretreatment methods are discussed and their effects on improvement in ethanol and production are described. They include milling, irradiation, microwave, steam explosion, ammonia fiber explosion (AFEX), alkaline hydrolysis, liquid hot-water pretreatment, wet oxidation, ozonolysis, diluteand concentrated-acid hydrolyses, and biological pretreatments. In this Review production of fuel ethanol from different raw materials are explained. The different technologies for producing fuel ethanol from sucrose-containing feed stocks (mainly sugar cane), starchy materials and lignocellulosic biomass are described along with the major research trends for improving them.